Glutaraldehyde and uranyl acetate dual fixation combined sputtering/unroofing enables intracellular fatty acids TOF-SIMS imaging with organelle-corresponding subcellular distribution. (28th June 2022) - Zhang, Chi; Horikawa, Makoto; Kahyo, Tomoaki; Matsudaira, Takaomi; Tanaka, Tatsuya; Xu, Lili; Takei, Shiro; Setou, Mitsutoshi
Abstract: Fatty acids (FAs) have diverse functions in cellular activities. The intracellular distribution of FAs is critical for their functions. Imaging of FAs by time-of-flight secondary ion mass spectrometry (TOF-SIMS) has been achieved. However, TOF-SIMS images of FAs so far do not have subcellular distribution due to inadequate sample preparation methods. In this study, we developed a chemical fixation method using glutaraldehyde (GA) with uranyl acetate (UA), which preserved cellular structure and intracellular FA distribution well. Combining GA+UA fixation with sputtering-based methods and unroofing-based methods, respectively, we successfully imaged intracellular lipids with the subcellular distribution.